Factors influencing immunogenicity and safety of SARS-CoV-2 vaccine in liver transplantation recipients: a systematic review and meta-analysis - Luo, Xinyi; Lessomo, Fabrice Yves Ndjana; Yu, Zhimin; Xie, Yong (Frontiers in Immunology, 2023)
Background: This review summarizes the factors influencing the efficacy and safety of the COVID-19 vaccine in LTR through meta-analysis, hoping to provide strategies for vaccine use.Methods: Electronic databases were screened for studies on mRNA vaccines in LTR. The primary outcome was the pooled seroconversion rate, and the secondary outcome was the incidence of adverse events+breakthrough infections. Subgroup analyses were made based on BMI, associated comorbidities, presence of baseline leukopenia, time since transplant, and drugs used.In total, 31 articles got included. The pooled seroconversion rate after at least two doses of SARS-CoV-2 vaccination was 72% (95% CI [0.52-0.91). with With significant heterogeneity among studies I 2 =99.9%, the seroconversion rate was about 72% (95%CI [0.66-0.75]), from the studies reporting two doses of vaccine slightly higher around 75%(95%CI [0.29-1.22]) from studies reporting three doses. The pooled seroconversion rate within the lower to normal BMI group was 74% (95% CI [0.22-1.27], Pi=0.005) against 67% (95% CI [0.52-0.81], Pi=0.000) in the high BMI group. The pooled seroconversion rate in the ''positive leukopenia'' group was the lowest, 59%. Leukopenia could influence the vaccine seroconversion rate in LTR. From the time since transplant analysis after setting seven years as cut off point, the pooled seroconversion rate after at least 2 two doses of COVID-19 vaccination was 53% (95% CI [0.18-0.83], P=0.003, I 2 =99.6%) in <7years group and 83% (95% CI [0.76-0.90], P=0.000 I 2 =95.7%) in > 7years group. The only time since transplantation had reached statistical significance to be considered as a risk factor predictor of poor serological response (OR=1.27 95%CI [1.03-1.55], P=0.024). The breakthrough infection rate after vaccination was very low2% (95% CI 0.01-0.03, I 2 =63.0%), and the overall incidence of adverse events, which included mainly pain at the injection site and fatigue, was 18% (95%CI [0.11-0.25], I 2 =98.6%, Pi=0.000).The seroconversion rate in LTR vaccinated with at least two doses of mRNA COVID-19 vaccine, could be significantly affected by the vaccine type, immunosuppressant used, BMI, leukopenia, associated comorbidities, and time since transplantation. Nevertheless, booster doses are still recommended for LTR.